Rezension von: Maack, Annelore, Protected by the enemy - Fritz, Gerhard (Backnanger Jahrbuch, 2002)
Annelore Maack: Protected by the Enemy. My Life with the P. O. W.s! San Francisco: Robert D. Reed Publishers, 2000, 220 S.